Reasons for dropout in youth soccer: a comparison with other team sports - O. Molinero; A. Salguero; E. Álvarez; S. Márquez (Asociación Española de Ciencias del Deporte, 2010)
The purpose of our study was to identify the main reasons for dropout in young soccer players and to compare withdrawal motives to those rated important by participants in other team sports. Dropouts (150 males and 159 females, ranging in age from 14 to 18 years) were administered the Questionnaire of Reasons for Attrition by Gould, Feltz, Horn and Weiss (1982). Represented were youth who participated in the sport of soccer (n=127), basketball (n=122), and volleyball (n=60). The most important reasons for attrition from the different team sports were having other things to do, dislike of the coach, and lack of team spirit. Reasons related to the team work were also given high ratings. Less important reasons concerned old age, rewards and competition. Although discriminant analysis revealed some differences between sports, the finding remains that both conflict of interests and aspects of the sports environment are major motives for withdrawal from team sports. Key Words: Dropout, team sport, soccer.